The Preservation of Bugis Language in Sinjai City: A Sociolinguistic Perspective - Nurhadi Hamka; Nurul Imansari; La Ode Achmad Suherman (Hasanuddin University, 2024)
The Bugis language, belonging to the Austronesian family, serves as a crucial element of cultural identity and heritage for the Bugis ethnic group in Indonesia, particularly in Sinjai City. However, like many indigenous languages, Bugis faces challenges in preservation due to socio-cultural factors. This research delves into preservation efforts and sociolinguistic dynamics surrounding the Bugis language since 2000, aiming to provide insights for stakeholders. Drawing on qualitative methods, including semi-structured interviews and ethnographic observations, this study aims to explore the motivations driving preservation efforts, investigate the role of education, examine socio-cultural factors influencing language use, and assess the effectiveness of existing preservation strategies. Findings reveal that cultural identity maintenance, intergenerational transmission, and the desire to safeguard linguistic diversity are primary motivations. Education emerges as pivotal, though hindered by the dominance of Bahasa Indonesia and limited institutional support. Socio-cultural factors like urbanization, migration, media influence, and linguistic stigma further challenge preservation. Strengths of current strategies include community engagement and cultural affirmation, while limitations include lack of support and linguistic stigma. Recommendations for augmenting preservation efforts include advocating for policy reforms, community empowerment, digital resources, and promoting multilingualism. Ultimately, preserving the Bugis language entails a holistic approach that honors cultural diversity and empowers the Bugis community.